Role of Imaging in Diagnosis and Management of COVID-19: A Multiorgan Multimodality Imaging Review - Varadarajan, Vinithra; Shabani, Mahsima; Ambale Venkatesh, Bharath; Lima, Joao A. C. (Frontiers in Medicine, 2021)
In this pandemic of Coronavirus disease (COVID-19), a vast proportion of health care resources including imaging tools have been dedicated to management of affected patients; yet, the frequent reports of unknown presentations and complications of disease over time, have been changing the usual standard of care and resource allocation in health centers. As of now, we have witnessed multi-systemic symptoms, requiring the collaboration of different clinical teams in COVID-19 patients’ care. Compared to the time of previous viral pandemics, imaging modalities are now playing a more essential role in diagnosis and management of patients. This widespread utility of imaging modalities calls for a deeper understanding of potential radiologic findings in this disease and identification of the most compatible imaging protocol with safety precautions. Although initially used for respiratory tract evaluation, imaging modalities have been also used for cardiovascular, neurologic, and gastrointestinal evaluation of patients with COVID-19. In this review article, we provide a multi-modality and multi-systemic review of imaging techniques and features that can aid in diagnosis and management of COVID-19 patients.